Assessment of CEPH-Accredited Institutions Offering Public Health Programs in the United States: A Short Report - Joshi, Ashish; Amadi, Chioma T. (Frontiers in Public Health, 2016)
Aims: Examine the distribution of the CEPH accredited institutions offering public health educational programs in the United States, and characterize their various attributes. Methods: A search was conducted during the period of June 2014, using the Association of Schools and Programs of Public Health database (ASPPH), and individual university websites to obtain a complete list of CEPH accredited institutions offering programs in Public Health at the Certificate, Masters, and Doctoral levels in the United States. Detailed information were abstracted from the various programs offerings including: school/program information, school type, geographic location, admission cycle, education delivery format, public health concentration, number of credits, presence of a global component, joint programs and tuition. The data was analyzed in August 2014. Results: A total of 85 CEPH accredited institutions designated as either “Schools of Public Health”, or individual “Programs of Public Health” were present in the ASPPH database at the time of this data collection (2014). These institutions offer programs in public health at the Certificate (61%, n=52), Masters (100%, n=85) and Doctoral (44%, n=37) levels in the US. More than half of the programs offered were provided by schools of public health (58%, N=49), which were mostly public universities (75%, n=64), concentrated in the Northeast (22%, n=19) and mainly admitted students during the fall semester. Ninety three concentrations of Public Health currently exist, of which 25 concentrations are predominant. Conclusion: To the best of our knowledge, this is the first study which examines the distribution of existing CEPH accredited Public Health educational programs offered by US institutions. We suggest future areas of research to assess existing Public Health workforce demands, and map them to the curriculums and competencies provided by institutions offering Public Health educational programs in the United States. This could provide valuable insight on the extent to which public health curriculums are meeting workforce demands.